WhatsApp conversations and relationships : a focus on digital communication between parent-teacher engagement in a secondary school in Putrajaya - Suriana Johari,; Wan Norbani Wan Noordin,; Tengku Elena Tengku Mahamad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Long before Covid-19 transitioned in our lifestyle and the ‘New Normal’ began, digital communication through instant messaging application in smartphones has been used over the conventional way of communicating in Malaysia. WhatsApp is the most preferred application when it comes to communicating with peers, friends and family and that is also true for schools in Malaysia, especially in the Klang Valley. The present study aims to investigate the use of digital communication focusing on parent-teacher engagement in a public school in Putrajaya, Malaysia that uses WhatsApp as the application of choice. This qualitative research employs in-depth interviews to collect data to describe the themes that have emerged in the discussion between parents and teachers on WhatsApp as a medium of communication in parent-teacher engagement process. This study incorporates theories such as Uses and Gratifications Theory (UGT) and Epstein’s Theory of Overlapping Sphere’s of Influences (TOSI) in describing the data. The results suggest that both parents and teachers agree on the importance of using digital platform for communication and engagement between them. The versatility of digital communication, convenience, speed and cost effectiveness are the reasons for using digital communication. However, the challenges for teachers that have been identified in the use of digital communication are increase of stress, distractions of messages and abuse of working time. Theoretical and practical implications for academics, parents, teachers and students were also included in the study.